Endo-Helminth Fauna of the Rainbow Lizard (Agama Agama) - Belema Robert; Nioking Amadi; Chidinma Charity Amuzie; Adaobi Patricia Ugbomeh (Journal La Lifesci, 2020)
This parasitological study was carried out between February and May 2019 to determine the prevalence and intensity of helminthiasis in the rainbow lizard (Agama agama) in Okrika, Rivers State, Nigeria. A total of one hundred and fifty-one (151) specimens made up of 93 males and 75 females were caught by a local netting system during the day and anaesthesized with chloroform. Samples were collected from two stations (Ogoloma-Ama and Oba-Ama). After dissection, the esophagus, stomach, small intestine, rectum, liver, lungs, urinary bladder, heart and body cavity were searched for helminths using conventional methods. Five species of helminths belonging to Nematoda - Strongyluris brevicaudata, Parapharyngodon awokoyai, encysted Ascaridida larva, Cestoda - Oochoristica sp. and Trematoda - Mesocoelium spp - were recovered from infected lizards. Helminths infected one hundred and twenty-three (123) (82%) of the lizards. In Oba-Ama, forty-five (45) (76.3%) out of 59 and in Ogoloma-Ama, seventy-eight (78) (84.8%) out of 92 were infected with helminths. By abundance, in both locations, the males were more infected than their female counterparts with a prevalence of 51(93%) and 72(75%) (P<0.05), respectively. This study has revealed the helminth parasites infecting the agamid lizard of Rivers State, Nigeria. It has also shown some unidentified species of Mesocoelium and Oochoristica sp. Additionally the trapping system used was also found to be effective and efficient.